Strategi Coping Stres pada Ibu Single Parent Pasca Ditinggal Suami Merantau - Yustina Pratiwi Nabit; M.K.P Abdy Keraf; Dian Lestari Anakaka (Journal of Health and Behavioral Science, 2019)
This research is aimed at examining coping stres strategies for single parent mother after separation from their husband who were leaving for work outside of the region. The methodology applies a qualitative research with the phenomenology approach. The participants during the interview were single parents mothers with charaterictics: a) they have been separated from their husband who work outside of the region, b) they age are in their fourties-fifties, c) they live in Oenaunu village. Methods of data analysis consisted of analysis before fieldresearch and analysis during the field research using Miles and Huberman model. The result showed that coping stres strategies used by participans were emotional focused coping and problem focused coping. The first and third partisipan tend to use emotional focused coping and problem focused coping as their coping strategy, while the second participant tends to use emotional focused coping and problem focused coping in her case.